2007
DOI: 10.1080/07366290701285538
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Palladium(II) with Various Ketones from Nitric Acid Medium

Abstract: Solvent extraction of Pd(II) with various ketones in nitrobenzene from nitric acid medium was investigated. In this study, seventeen commercially available ketones were selected as representatives of alkyl ketones. It was found that several ketones effectively extracted Pd(II) from nitric acid medium. Methylalkylketones, such as 2-octanone, 2-nonanone, 2-undecanone, 2-tridecanone, and ketones containing symmetrical alkyl configuration, such as 5-nonanone, 5-decanone, 5-undecanone, and 6-undecanone exhibited si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Several appropriate technologies are available including precipitation (Safdar et al, 2011), solvent extraction (Hung et al, 2007;Shamsipur et al, 2009), membrane filtration (Borbély and Nagy, 2009;Trivunac and Stevanovic, 2006;Xiang Li et al, 2013), cementation (Aktas, 2011(Aktas, , 2012Morcali et al, 2013c), ion exchange (Godlewska-Żylkiewicz et al, 2000;Shen et al, 2010Shen et al, , 2011 and adsorption (Fırlak et al, 2013;Kyzas et al, 2013;Wang et al, 2011). Comparatively, adsorption seems to be the most suitable as large volumes of very dilute wastes can be treated economically and nearly no waste residue is produced (Morcali et al, 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…Several appropriate technologies are available including precipitation (Safdar et al, 2011), solvent extraction (Hung et al, 2007;Shamsipur et al, 2009), membrane filtration (Borbély and Nagy, 2009;Trivunac and Stevanovic, 2006;Xiang Li et al, 2013), cementation (Aktas, 2011(Aktas, , 2012Morcali et al, 2013c), ion exchange (Godlewska-Żylkiewicz et al, 2000;Shen et al, 2010Shen et al, , 2011 and adsorption (Fırlak et al, 2013;Kyzas et al, 2013;Wang et al, 2011). Comparatively, adsorption seems to be the most suitable as large volumes of very dilute wastes can be treated economically and nearly no waste residue is produced (Morcali et al, 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…2 In this context, the extraction of Pd(II) from nitric acid medium with various ketones in nitrobenzene has been reported. 3 The authors concluded that both methylalkylketones and ketones containing symmetrical alkyl configuration effectively extracted Pd(II) from nitric acid medium, especially 2-tridecanone and 2-nonanone which exhibited efficient extraction of Pd(II) and provided a feasible extraction system at 3.0 M ligand concentration and HNO 3 above 2.0 M.…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature has included several methods for the recovery of precious metals (i.e., platinum, palladium, rhodium, ruthenium, osmium, iridium, gold, and silver) from aqueous solutions, such as solvent extraction (Shamsipur et al 2009;Hung et al 2007), ionexchange (Shen et al 2010;Godlewska-Żylkiewicz et al 2000;Shen et al 2011), filtration (Li et al 2013;Trivunac and Stevanovic 2006;Borbély and Nagy 2009), cementation (Aktas 2012;Morcali et al 2013a), and adsorption Kyzas et al 2013;Morcali et al 2013b). Among these methods, adsorption is the most suitable method for the recovery of precious metals due to its low cost, ease in handling, high efficiency, reversibility, and the availability of different adsorbents.…”
Section: Introductionmentioning
confidence: 99%